Organic Compounds and Inorganic Metals Removal from Wastewater Using Klebsiella pneumoniae and Acinetobacter lwoffii (Journal of Nuclear Technology in Applied Science, 2018)
Wastewater contains high levels of organic material, numerous  pathogenic microorganisms, as well as nutrients and toxic compounds.  Wastewater samples were collected from influent of different wastewater  treatment plant. Klebsiella pneumoniae and Acinetobacter lwoffii were  isolated from the samples and these isolates were screened for the re duction of wastewater components which estimated by COD (Chemical  Oxygen Demand), BOD (Biological Oxygen Demand), and TSS (Total  Suspended Solids) values. Wastes reduction by the isolated bacteria using  different pH values, incubation temperatures, inoculum volume, static  and dynamic condition with different incubation periods and bioremedia ion the variable concentrations of metals in singles and mixtures states  were studied. Our investigate show the optimum conditions at pH 7, 35˚C,  dynamic condition, 0.5% standard inoculum volume for K.pneumoniae and 2% for A.lwoffii, 48 hours’ incubation period, and metals concentra tions 5ppm.
Keywords: Abu Rawash Wastewater Plant; Klebsiella pneumonia; Acinetobacter lwoffii; Heavy Metal; Mineral Silica Oil (MSO); Tryptic Soy Agar (TSA)